Role of Gut Microbota in Etiopathogenesis of Chronic Intestinal Psueudo Obstruction - Giulia Radocchia; Bruna Neroni; Massimiliano Marazzato; Elena Capuzzo; Simone Zuccari; Fabrizio Pantanella; Letizia Zenzeri; Melania Evangelisti; Francesca Vassallo; Pasquale Parisi; et al. (Research Perspectives of Microbiology and Biotechnology Vol. 2, 2024)
The present study discusses current literature regarding the relationship between gut microbiota, CIPO patients and intestinal motility, suggesting that future studies could be important for better comprise the causes of intestinal motility dysfunction in CIPO patients. Chronic intestinal pseudo-obstruction (CIPO) is a rare clinical syndrome characterized by severe impairment of gastrointestinal (GI) motility and its symptoms are suggestive of partial or complete intestinal obstruction in absence of any lesion restricting the intestinal lumen. Diagnosis and therapy of CIPO patients still represent a significant challenge for clinicians, despite their efforts to improve diagnostic workup and treatment strategies for this disease. Motility in the GI tract is controlled by the enteric nervous system (ENS), CIPO patients could be affected by alterations of the ENS. Furthermore, a recent pilot study has also highlighted, for the first time, a specific intestinal mucosa associated microbiota, and an altered expression of intestinal serotonin-related genes in CIPO patients. The purpose of this review is to better understand what is currently known about the relationship between CIPO patients and intestinal microbiota, with a focus on the role of the enteric nervous system (ENS) and the intestinal endocrine system (IES) in intestinal motility, underling the importance of further studies to deeply understand the causes of gut motility dysfunction in these patients.